PENYULUHAN MENGENAI KEBERLANJUTAN USAHA PERIKANAN TANGKAP SKALA KECIL BERDASARKAN ASPEK EKONOMI DI OHOI OHOIDERTAWUN KABUPATEN MALUKU TENGGARA - Picaulima, S.M.; Notanubun, J.; Kilmanun, A.D. (Buletin Udayana Mengabdi, 2023)
This community service carried out in Ohoi Ohoidertawun aims to provide an understanding of the sustainability of small-scale fishery businesses based on economic feasibility status which includes business financial aspects and business capital investment, so that small-scale fisheries businesses in the future can run well and profitably. The method of service is counseling which includes discussion and question and answer. The results obtained indicate that the counseling carried out was successful. Participants of small fishing partners and government staff of Ohoi Ohoidertawun were very enthusiastic in participating in the delivery of counseling materials delivered by the service team so that when the evaluation was carried out at the end of the activity the participants were able to answer questions properly and correctly. The problem faced by partner fishermen is that the business income of small fishermen partners is very dependent on the fishing season so that small-scale capture fisheries business in the future is difficult to predict. The status of fishery business feasibility includes business financial feasibility and business investment feasibility. This activity went well, smoothly and full of good interactions between the service team and participants, the results of this activity have increased the understanding of small fishermen partners regarding the sustainability of small-scale capture fisheries in Ohoi Ohoidertawun. Keywords: Sustainability, Small fishermen, Business viability, Business finance, Business investment.